Aleksis Kivi and/as world literature - Robinson, Douglas, 1954- (Approaches to translation studies., 2017)
"Aleksis Kivi (1834-1872) is Finland's greatest writer. His great 1870 novel The Brothers Seven has been translated 58 times into 34 languages. Is he world literature, or not? In Aleksis Kivi and/as World Literature Douglas Robinson uses this question as a wedge for exploring the nature and nurture of world literature, and the contributions made by translators to it. Drawing on Deleuze and Guattari's notion of major and minor literature, Robinson argues that translators have mainly 'majoritized' Kivi -- translated him respectfully -- and so created images of literary tourism that ill suit recognition as world literature. Far better, he insists, is the impulse to minoritize -- to find and celebrate the minor writer in Kivi, who 'sends the major language racing' "--